The Induction of Primary and Secondary Somatic Embryo to Support Arabica Coffee Propagation - Ibrahim, Meynarti Sari Dewi; Hartati, Raden Roro Sri; Rubiyo, Rubiyo; Purwito, Agus; Sudarsono, Sudarsono (Department of Agronomy and Horticulture, IPB University, 2015)
The primary and secondary somatic embryogenesis can be used to propagate Coffea arabica L clonally. However, the success of this propagation was depended on plant growth regulator and varieties. This study aimed to examine the possibility of 2,4-D and thidiazuron application to form primary and secondary somatic embryo to support Arabica coffee clonal propagation. The study consisted of two activities (1) 2,4-D and thidiazuron Application to Induce Primary Somatic Embryogenesis of Arabica Coffee and (2) The Application of thidiazuron in Solid and Semi-Solid Media to Induce Secondary Somatic Embryos. The results indicated significant effect of varieties and plant growth regulator on fresh weight, number of torpedo and germinated embryo. However, it showed no significant effect on callus formation percentage. The best medium to induce primary somatic embryogenesis depending on variety, on the treatment of 4.52 μM 2,4 -D +18.16 μM thidiazuron was the best for AS2K and Sigarar Utang varieties, S 795 at 4.52 μM 2,4-D + 9.08 μM thidiazuron, whereas Kartika at 4.52 μM 2.4-D + 13.62 μM thidiazuron. The morphology of coffee somatic embryo was normal. Primary somatic embryo was developed indirectly, whereas the secondary somatic embryo was directly. The application of 9.08 μM thidiazuron increased the percentage and number of secondary somatic embryos, hence enhancing number of Arabica coffee planlet. Keywords : Coffea arabica L, 2,4-D, thidiazuron, semi-solid media, Indirect somatic embryogenesis